(3QSGdI aj GdefWbs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3gPg QSGdI YedgG ajeJ JbQQ YfOi ef GdMcheI ai MLL GdefTFjf ddeGVi eHOCg ReGffG hbO bSeJ gPg GdebGdI Edi aUhd CMO YTQ ai JYOjO CUfGa GdebOeGJ s
(3BNQgG (B:s
(3BNQ GdehLhO efgG bhdg (B: (3GdaUd GdKGdK ai JYQja UhQI bjGSGJ gi Chdi GdbjGSGJ gh eLJeY GdMOjf GdBNQjf aJchf GdCTcGd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdJGSY hGdYTQhfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ , JGeI s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdadSaI hGdefWbs